PEMANFAATAN TEPUNG DAUN PEPAYA (Carica papaya.L L ess) DALAM UPAYA PENINGKATAN PRODUKSI DAN KUALITAS TELUR AYAM SENTUL - Tuti Widjastuti (Universitas Tadulako, 2009)
An experiment on the use of Carica papaya leaf meal to increase the production and quality of Sentul chicken eggs was carried out in Jelekong village, Baleendah Subdistrict, Bandung District. Seventy five Sentul Chicken at 36 weeks of age were used. Data were analyzed using a Completely Randomized Design consisted of five treatments including Carica papaya leaf meal of 0, 2.5, 5, 7.5 and 10%. The result indicated that the use of Carina papaya leaf meal in ration up to 10 percent did not significantly affect egg production, egg weight, Haugh unit value, and shell thickness, but the use of 10 percent Carina papaya leaf meal in ration significantly affected color yolk score.